Pravo i društvena stvarnost / Law and Social Reality: Muslimani u monarhističkoj Jugoslaviji / Muslims in Monarchistic Yugoslavia - Bandžović, Safet (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
This text is the review of a book Muslims of Yugoslavia after the Great War – impacts of Saint-Germain Peace Treaty 1919 (Institute for Bosniak islamic tradition, Sarajevo, 2020, pages: 361).